2020
DOI: 10.1182/bloodadvances.2020001956
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic stem cell transplantation for chronic lymphocytic leukemia in the era of novel agents

Abstract: Although novel agents (NAs) have improved outcomes for patients with chronic lymphocytic leukemia (CLL), a subset will progress through all available NAs. Understanding outcomes for potentially curative modalities including allogeneic hematopoietic stem cell transplantation (alloHCT) following NA therapy is critical while devising treatment sequences aimed at long-term disease control. In this multicenter, retrospective cohort study, we examined 65 patients with CLL who underwent alloHCT following exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 62 publications
2
58
0
1
Order By: Relevance
“…6 However, few studies have investigated the possible impact of previous exposure to these novel agents on HSCT outcomes. [7][8][9] With this study, we aimed to help further determine the impact of exposure to novel agents on post-HSCT outcomes in patients with CLL and those with CLL-RT.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, few studies have investigated the possible impact of previous exposure to these novel agents on HSCT outcomes. [7][8][9] With this study, we aimed to help further determine the impact of exposure to novel agents on post-HSCT outcomes in patients with CLL and those with CLL-RT.…”
Section: Introductionmentioning
confidence: 99%
“…In the modern era, allogeneic hematopoietic stem cell transplant has become safer and more accessible. Recent retrospective analyses of transplant outcomes in CLL reported 2-year PFS of 63% ( 125 ) and 3-year non-relapse mortality of 7% in patients who were previously treated with targeted agents ( 126 ). Treatment with CD19 CAR T can also achieve high rates of initial response in patients who failed ibrutinib ( 115 ).…”
Section: Overcoming Resistance To Covalent Btk Inhibitorsmentioning
confidence: 99%
“…In this study, the investigators observed that PFS was predicted by the hematopoietic cell transplantation-specific comorbidity index. No differences were observed among the patients receiving previous TA (one or two ibrutinib/venetoclax) or TA and CIT as the previous treatment [ 235 ]. Currently, most guidelines recommend it for patients with high-risk CLL that have relapsed or are refractory to at least one TA or in cases of clonally related Richter transformation with a response to chemotherapy [ 202 , 236 ].…”
Section: Treatmentmentioning
confidence: 99%